Estimates of the heat kernel on a manifold of nonpositive curvature - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
On a Riemannian manifold of nonpositive curvature, we obtain dimension-independent estimates for the fundamental solution of a parabolic equation and for the logarithmic derivative of this solution.